Pengembangan Aplikasi Pendaftaran Pasien dan Notifikasi Perubahan Jam Praktik Dokter pada Klinik XYZ - Winanti, Winanti; Kirana, Komalasari Indah; Suwita, Jaka; Nurasiah, Nurasiah (Program Studi Teknik Informatika Universitas Pamulang, 2024)
The problem that XYZ Clinic has been facing so far is problems in the registration section where there are often long queues. Patient registration can only be done by coming directly to the XYZ clinic. Every day the average number of patients reaches 100 patients, which results in long queues and disrupted patient registration services. The number of patients that is not proportional to the number of registration officers also causes quite long waiting times during registration, causing discomfort and patient dissatisfaction. Research was carried out regarding the registration information system and notification of changes to doctors' schedules using the PHP programming language and MySQL database and system development was carried out using the SDLC (System Development Life Cycle) method with the prototype method. This method has an approach with communication stages, quick design and modeling, quick design, construction of prototype, deployment and feedback. The Patient Registration Application and Notification of Changes in Doctor's Practice Hours are expected to reduce long queues and patient waiting times. Patients can find out in advance the availability and order number by accessing the website from home, equipped with a WhatsApp notification feature for changes in the doctor's schedule and patients can adjust the time to go to the clinic for treatment according to the latest schedule provided via the application.